Diagnostic radiation exposure of injury patients in the emergency department: a cross-sectional large scaled study. - Je Sung You (Public Library of Science (PLoS), 2013)
In contrast to patients with underlying cancer or chronic disease, injury patients are relatively young, and can be expected to live their natural lifespan if injuries are appropriately treated. Multiple and repeated diagnostic scans might be performed in these patients during admission. Nevertheless, radiation exposure in injury patients has been overlooked and underestimated because of the emergent nature of such situations. Therefore, we tried to assess the cumulative effective dose (cED) of injury patients in the emergency department. We included patients who visited the emergency department (ED) of a single tertiary hospital due to injury between February 2010 and February 2011. The cED for each patient was calculated and compared across age, sex and injury mechanism. A total of 11,676 visits (mean age: 28.0 years, M:F = 6,677:4,999) were identified. Although CT consisted of only 7.8% of total radiologic examinations (n=78,025), it accounted for 87.1% of the total cED. The mean cED per visit was 2.6 mSv. A significant difference in the cED among injury mechanisms was seen (p<0.001) and patients with traffic accidents and fall down injuries showed relatively high cED values. Hence, to reduce the cED of injury patients, an age-, sex- and injury mechanism-specific dose reduction strategy should be considered.